2016
DOI: 10.1088/1742-5468/2016/04/043305
|View full text |Cite
|
Sign up to set email alerts
|

Corner transfer matrices for 2D strongly coupled many-body Floquet systems

Abstract: We develop, based on Baxter's corner transfer matrices, a renormalizable numerically exact method for computation of the level density of the quasi-energy spectra of two-dimensional (2D) locally interacting many-body Floquet systems. We demonstrate its functionality exemplified by the kicked 2D quantum Ising model. Using the method, we are able to treat the system of arbitrarily large finite size (for example 10000 × 10000 lattice). We clearly demonstrate that the density of Floquet quasi-energy spectrum tends… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…8 with the correspondence H kick → T 1 H 1 . This equivalent formulation makes the link with the literature on kicked quantum models which have a long history in the field of quantum chaos (see [3,6,8,11] and references therein).…”
Section: B Periodically-kicked Quantum Spin Chainmentioning
confidence: 94%
“…8 with the correspondence H kick → T 1 H 1 . This equivalent formulation makes the link with the literature on kicked quantum models which have a long history in the field of quantum chaos (see [3,6,8,11] and references therein).…”
Section: B Periodically-kicked Quantum Spin Chainmentioning
confidence: 94%
“…Namely, information can spread only by one site, left or right, within one period (kick of the magnetic field). Random matrix analysis [49,50] revealed that KI is chaotic.…”
mentioning
confidence: 99%
“…A key obstacle in the search for new non-equilibrium quantum phases of matter is the tendency of closed quantum many-body systems to indefinitely absorb energy from a time-periodic driving field. Thus, in the long time limit, such systems generically reach a featureless infinite-temperature-like state with no memory of their initial conditions [1][2][3][4][5][6][7][8]. Interestingly, this infinite temperature fate can be avoided by the addition of disorder [9][10][11][12][13].…”
mentioning
confidence: 99%